臼後部に発生した多形腺腫の1例 - 中村, 誠司; 鈴木, 華子; 川野, 真太郎; 後藤, 雄一; 吉賀, 大午; 小林, 家吉 (日本口腔外科学会雑誌, 2012)
Pleomorphic adenoma is one of the most frequent salivary gland tumors. Pleomorphic adenoma derived from minor salivary glands most commonly occurs in the palate. However, few reports have described pleomorphic adenoma arising in the retromolar region. We describe a rare case of pleomorphic adenoma that developed in the retromolar region. The patient was a 68-years-old woman presenting with a painless mass in the retromolar region. The preoperative results of biopsy at another hospital and imaging examinations showed a pleomorphic adenoma. Under general anesthesia, the tumor mass was removed with adequate surgical margins, including the periosteum. The final pathological diagnosis of the extirpated specimen was pleomorphic adenoma. Follow-up examinations have shown no evidence of recurrence for 1 year 9 months after surgery. To our knowledge, only 5 similar cases have been reported in Japan. Moreover, among 223 salivary tumors treated in our hospital, there were only 2 cases (0.9%) of pleomorphic adenoma of the retromolar region.